2022
DOI: 10.3389/fnut.2022.892675
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Undernutrition and Risk of Undernutrition in Overweight and Obese Older People

Abstract: Older people with excess body weight are not spared from undernutrition. They may face appetite decline which may lead to insufficient nutrient intake. They also have a higher risk of developing chronic diseases which may have a negative impact on protein-anabolic pathways. The present study aimed to determine the prevalence of undernutrition in overweight and obese older people from a secondary analysis on data collected through two French surveys among people aged 65 or over (n = 782; 31% men; 65–103 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Another reason could be that systemic inflammation caused by obesity affects the absorption, distribution, and excretion of nutrients, thereby altering micronutrient metabolism ( 41 ). A study conducted among 782 French older adults (aged ≥65 years) found that 18% of overweight and 29% of obese individuals were at risk of undernutrition ( 42 ). Furthermore, in contrast with studies from India ( 6 ), Bangladesh ( 19 ), and France ( 42 ) that reported higher malnutrition rates among women than among men, we found that more men than women were at risk of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason could be that systemic inflammation caused by obesity affects the absorption, distribution, and excretion of nutrients, thereby altering micronutrient metabolism ( 41 ). A study conducted among 782 French older adults (aged ≥65 years) found that 18% of overweight and 29% of obese individuals were at risk of undernutrition ( 42 ). Furthermore, in contrast with studies from India ( 6 ), Bangladesh ( 19 ), and France ( 42 ) that reported higher malnutrition rates among women than among men, we found that more men than women were at risk of malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among 782 French older adults (aged ≥65 years) found that 18% of overweight and 29% of obese individuals were at risk of undernutrition ( 42 ). Furthermore, in contrast with studies from India ( 6 ), Bangladesh ( 19 ), and France ( 42 ) that reported higher malnutrition rates among women than among men, we found that more men than women were at risk of malnutrition. A possible explanation for this might be that only 49% of women but the majority of men (92%) in our study were dependent on their families for food preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of BMI to the model provided little additional predictive power. This is perhaps not surprising, as BMI appears not to be associated with protein-energy malnutrition in older adults (van der Pols-Vijlbrief et al, 2014), and between 20 and 35% of older adults with a BMI of greater than 25 kg·m -2 are at risk of undernutrition (Klee Oehlschlaeger et al, 2014; Özkaya & Gürbüz, 2019; Sulmont-Rossé et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is acknowledged that under‐reporting is an issue in all nutritional surveys including in older adults (Public Health England, 2018b ) and data on energy intake is not consistent with data on levels of obesity, which in the United Kingdom lie at 36% of adults aged 65–74 years and 26% of adults aged 75 years and over (Health Survey for England, 2019 ). Nevertheless, a recent study by Sulmont‐Rossé et al ( 2022 ) looked at the prevalence of undernutrition in older people (65 years and over) living with overweight and obesity by completing a secondary analysis of data collected through two French surveys. It indicated that 2% of the respondents with a body mass index over 25 kg/m 2 were undernourished, but that 18% of those overweight and 29% of those with obesity were at risk of undernutrition using the Mini‐Nutritional Assessment (MNA) Screening tool.…”
Section: Nutritional Requirements and Older Adults: Where Evidence An...mentioning
confidence: 99%